An assessment of the diabetic knowledge of school teachers. Issue 9 (September 1983) - Bradbury, A J; Smith, C S
Abstract : Ninety seven teachers of diabetic pupils in Liverpool completed a questionnaire designed to assess their knowledge of diabetes mellitus and the sources from which they had obtained information. The survey aimed to evaluate their understanding and to aid in planning an alternative policy of teacher education. Only 24 teachers (25%) seemed to have adequate understanding of diabetes and there was little knowledge of recognition and treatment of emergency diabetic problems and aspects of diet. Most information had been obtained from either diabetic pupils or their parents and not from medical or nursing personnel.